2005
DOI: 10.1007/s00277-005-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of rituximab as a salvage therapy for HIV-associated multicentric Castleman disease

Abstract: Several approved therapies for multicentric Castleman disease (MCD) cannot be uniformly applied due to intolerable side effects. There is also a high percentage of recurrence of this disease despite treatment. Rituximab may be effective in controlling MCD in a subset of patients. This paper includes a brief case report and an extensive review of previously published cases. We observed an aggravation of concomitant cutaneous Kaposi sarcoma, and hypothesize that rituximab could have exacerbated it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
0
16
0
1
Order By: Relevance
“…Although HHV-8-infected plasmablasts frequently do not express high levels of CD20, it has been speculated that rituximab is effective in HIV-MCD by eliminating or reducing the pool of HHV-8-infected B cells, which are localized mainly in the mantle zone of lymph nodes. After initial case reports, [15][16][17][18] two recent pilot studies have evaluated rituximab in patients with HIV-MCD. In a French study, 19 16 of 24 patients reached a complete remission of clinical symptoms after 4 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Although HHV-8-infected plasmablasts frequently do not express high levels of CD20, it has been speculated that rituximab is effective in HIV-MCD by eliminating or reducing the pool of HHV-8-infected B cells, which are localized mainly in the mantle zone of lymph nodes. After initial case reports, [15][16][17][18] two recent pilot studies have evaluated rituximab in patients with HIV-MCD. In a French study, 19 16 of 24 patients reached a complete remission of clinical symptoms after 4 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,39,43,[45][46][47][48][49][50][51][52][53][54][55] Although rapid resolution of symptoms has been reported in patients with active disease, relapses occur frequently and the progression-free survival is often brief. A strategy using maintenance oral etoposide (100-200 mg/m 2 , weekly) has been adopted in France.…”
Section: Chemotherapymentioning
confidence: 99%
“…2,3 Manifestations of the disease are thought to be related in part to cytokine disarray, in particular increased levels of interleukin-6 (IL-6), a homologue of which is produced by the HHV-8 genome. 4,5 Treatment of HIV-MCD had been largely ineffective until a number of case reports [6][7][8][9][10][11] and 2 recent single-arm clinical trials showed that rituximab induces clinical remission in both persons at first presentation 12,13 and with pretreated and relapsed HIV-MCD. 14 Rituximabinduced B-cell depletion, a likely reservoir of HHV-8, has been postulated to occur via antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%